A Production Model with Continuous Demand for Imperfect Finished Items Resulting from the Quality of Raw Material - Nasr El Dine, Mohammad (2020)
This thesis aims to investigate the production process having different qualities of a single type of raw material which is utilized in the production process of the finished good. From preceding studies, researchers usually discarded the idea of including imperfect quality items in production. This thesis, however, regards the case in which the two types of raw material, the perfect and the imperfect qualities items, are not discarded but rather used in to produce the finished product. This consequently results in the production of two types of finished product, perfect and imperfect qualities, respectively. That being said, it is also assumed that the two types of finished products have continuous. It must be noted that this modeling approach still has not been researched. The development of two models that are subject to the inventory cycle length of each type of raw material is done in this thesis. For that, and to better illustrate how optimal production quantity is determined, numerical examples are provided. In this thesis, we present theoretical implications with recommendations being provided in the end.